Promoting Recovery from Substance Misuse through Engagement with Community Assets: Asset Based Community Engagement. (September 2019) - Collinson, Beth; Best, David
Evidence shows that engagement with community resources can aid the process of recovery from substance misuse, yet systematic approaches to mapping resources and building bridges to these for recovery populations are limited. If done successfully, engagement with resources that are pro-social and afford access to meaningful activities not only provides a platform for personal development, but also has the ability to trigger a social contagion of positive behaviour and improve connectedness within communities. The current paper uses Asset Based Community Development (ABCD) as the basis for an enhanced version called Asset Based Community Engagement (ABCE). The work of ABCD has been pivotal in encouraging citizen-led, strengths-based approaches to community development, yet scientific support for it remains limited. While this approach has gained much traction, it has been subject to criticism for being too optimistic and unsystematic. In response to this, the new framework, ABCE, offers a more structured approach to mapping community resources. It does however advance previous work by acknowledging the need to identify current levels of community engagement and barriers to engagement, in order to support empowerment, maximise personal capital and address barriers to engagement. Identifying barriers to engagement should not draw ABCE away from its strengths-based focus but instead, provide a platform for person-centred, holistic support to be provided to those in recovery. To support the new framework, a workbook has been developed, offering a practical output that is intended to be used by the individual in recovery alongside a member of staff within a professional service supporting the individual.